Master Installation Design And Transformer Need Analysis in Faculty of Engineering Udayana University Denpasar - Janardana, IGN; Wijaya, Wayan Arta (Journal of Electrical, Electronics and Informatics, 2020)
Faculty of Engineering, Udayana University, PB. Sudirman Denpasar has 5 building units (buildings A, B, C, D, AF). Currently the AF building is undergoing renovation and is planned to be on 4 floors. The entire building will be equipped with the installation of 2 elevator units. The construction of the two new buildings and the installation of the 2 elevator units caused new problems of electricity shortages, changes in safety settings, unbalanced loads, and changes in the size of the main cable and the needs of the transformer and its capacity. The AF building and building A are supplied from sources on the transformer which are joined with other faculties, while Buildings B, C, D and E are fed by one transformer No. 124303818 with a capacity of 160 kVA. The plan to build an Alumni Building does not yet have electricity. Based on the analysis of the design, the total amount of power needed in all buildings in the Sudirman Denpasar Faculty of Engineering is the result of the AF Building planning = 134,280 watts, the Alumni Building planning results (building area and building functions are considered equal = 134,280 watts), so the total needs power to the two buildings = 271 560 Watt with a load deviation of 65%, then 0.65 x 271 560 W = 176 514 Watt. Then the total power requirement of the entire building is 259,340 watts. The measurement result of Cos ? 0.92, then P (kVA) = 281,891,3043 Ampere = 281,8913 kVA. So that the transformer needs that must be prepared by the Faculty of Engineering to meet the power requirements at the Faculty of Engineering, Udayana University Denpasar with 80% transformer efficiency is a 350 kVA transformer with a placement position around the Faculty of Engineering area